Effects of ultrasound-assisted plasma-activated water pretreatment combined with electrohydrodynamics on drying characteristics, active ingredients and volatile components of yam (Dioscorea opposita) - Wurile Bai; Peng Guan; Jiaqi Liu; Junjun Lian; Zhiqing Song; Hao Chen; Ru Xing; Jingli Lu; Changjiang Ding (Ultrasonics Sonochemistry)
This paper explores the effect of ultrasound (US) assisted plasma-activated water (PAW) or deionized water (DW) pretreatment combined with electrohydrodynamics (EHD) on the drying of yam. The activity characteristics of four pretreatments (plasma activated water combined with ultrasound (PAW + US), plasma activated water (PAW), deionized water combined with ultrasound (DW + US), and deionized water (DW) (control)) and their effects on drying characteristics, rehydration rate, color, reducing sugars, total phenols, infrared spectra, and volatile compositions of yam under EHD drying process were investigated. The results showed that the media pretreaded by ultrasound (US) combined with plasma-activated water (PAW) has lower media of pH (53.84 % lower than that of US + DW), higher nitrite ion concentration (311 times over US + DW), higher oxidation reduction potential (50.58 % higher than that of US + DW), and higher electrical conductivity (99.29 times over US + DW). And ultrasonic pretreatment (US) combined with plasma-activated water (PAW) drying resulted in faster drying, better rehydration rate, higher brightness L * (18.35 % higher than that of US + DW) and whiteness (1.1 % higher than that of US + DW), and retention of more reducing sugars (10.96 % higher than that of US + DW) and total phenols (14.04 % higher than that of US + DW), and a higher variety and content of volatile components. This provides an experimental and theoretical basis for the application of ultrasonic (US) combined with plasma-activated water (PAW) pretreatment to electrohydrodynamic drying.